Crowdsourcing - Kacper Niburski (Voices in Bioethics, 2015)
In entrepreneurship, it isn’t what you have; it's how you sell it. But on crowdsourcing platforms such as Kickstarter or GoFundMe, it is becoming the case that what you have is what you sell: your body.